INTERAKSI PRODUK DAN PELAKU AGRIBISNIS HORTIKULTURA UNGGULAN JERUK SIAM BANJAR (Citrus reticulata) PROVINSI KALIMANTAN SELATAN - Husinsyah (Chlorophyl, 2022)
The purpose of this study was to analyze the factors that affect the level of production and horticultural income in South Kalimantan Province.. The condition of farmers' access to the largest is the affordable price of seeds, which is 65%, while the lowest is the ability of citrus farmers to adopt technology which is only 25%. the factors that influence the level of superior horticultural production are the number of seeds, the amount of fertilizer, the number of workers and the level of technology with the largest value being the number of workers at 4.336 and the lowest at the technology level being 2.259. the factors that influence the level of superior horticultural production are the number of seeds, the amount of fertilizer, the number of workers and the level of technology with the largest value being the number of workers at 4.336 and the lowest at the technology level being 2.259. The factors that influence the level of superior horticultural income in South Kalimantan Province, there are two factors that have a very significant influence, namely the transaction volume of 3,117 and the selling price of 3,648